Lipid profiles in major depression, both with and without metabolic syndrome: associations with suicidal behaviors and neuroticism - Ketsupar Jirakran; Asara Vasupanrajit; Chavit Tunvirachaisakul; Abbas F. Almulla; Marta Kubera; Michael Maes (BMC Psychiatry)
Abstract Background Significant associations exist between major depressive disorder (MDD), metabolic syndrome (MetS), and cardiovascular disease, potentially attributable to heightened atherogenicity. This study aimed to ascertain if MDD, depression severity, suicidal behaviors, and neuroticism associate with elevated pro-atherogenic indices and reduced anti-atherogenic indices, including a reverse cholesterol transport (RCT) index. Methods This study comprised 34 healthy controls and 33 MDD patients without MetS, and 35 controls and 31 MDD patients with MetS. It assessed total cholesterol (TC) and free cholesterol (FC), high-density lipoprotein cholesterol (HDLc), low-density lipoprotein cholesterol (LDLc), triglycerides (TG), apolipoprotein (ApoA), ApoB, cholesterol esterification rate, and a RCT composite. Results No significant associations between MDD and lipids were seen in the total study group that combined individuals with and without MetS. In individuals devoid of MetS, MDD is significantly correlated with (a) elevated FC, TG, ApoB, Castelli risk index 1, and ApoB/ApoA, and (b) diminished HDLc, ApoA, and RCT index. In individuals without MetS, there are notable correlations between the severity of depression, suicidal tendencies, neuroticism, and ApoB/ApoA, Castelli risk, and RCT indices. Conclusions The link between lipids and MDD features cannot be adequately estimated by combining participants with and without MetS. It should be examined in a study sample that excludes subjects with MetS. The depression phenome, suicidal behaviors, and neuroticism correlate with diminished RCT and heightened atherogenicity, which are likely implicated in the pathophysiology of MDD. Increased atherogenicity and lowered RCT may represent novel drug targets for the treatment and prevention of MDD, neuroticism, and suicidal behaviors.